Effect Of Workload, Satisfaction And Facilities On The Perfomance Of Nurse In The Treatment Of Floor Ii Mawar Tour Uit Hospital Makassar - Ahmad Hannani; Muzakkir - (Jurnal Mirai Management, 2016)
ABSTRACT The purpose of this study are: (1). To know and analyze the impact of workload on the performance of the nurse in the treatment room the second floor roses RSU Makassar Tourism UIT, (2). To know and analyze the impact of satisfaction on the performance of the nurse in the treatment room the second floor roses RSU Makassar Tourism UIT, (3) to determine and analyze the impact of the facility on the performance of the nurse in the treatment room the second floor roses RSU Makassar Tourism UIT. The research method used in this research is survey method with quantitative approach with cross sectional study approach using variables, both as independent variable and dependent variable. The sample used in this study is the population of 40. Data analysis is descriptively quantitative by using SPSS program of Multiple Linear regression analysis method. The results of research based on hypothesis test proves that (1). Workload has a positive and significant effect on the performance of Nurse In Raising Room of Floor II of UIT Makassar Hospital with standarized parameter value is 0.325 with significant value of 0.003. (2). Satisfaction has the positive and most significant effect on the performance of nurses in the second floor of treatment room of UIT Makassar RSU with the value of standarized parameter of 0383 with significant value 0.000. (3). Facilities have a positive and significant effect on the performance of nurses in the second floor of treatment room of UIT Makassar RSU with standarized parameter value of 0.383 with significant value of 0.002. The Satisfaction Variable has the most dominant variable. Keywords: Workload, Satisfaction, Facility